THE IMPORTANCE OF USING INNOVATIVE PEDAGOGICAL METHODS IN PHYSICS CLASSES IN THE DEVELOPMENT OF TECHNICAL ABILITIES OF STUDENTS OF THE TECHNICAL HIGHER EDUCATIONAL INSTITUTION - Goibova Nargiza Ziyoxonovna (Research Focus International Scientific Journal, 2023)
THE IMPORTANCE OF USING INNOVATIVE PEDAGOGICAL METHODS IN PHYSICS CLASSES IN THE DEVELOPMENT OF TECHNICAL ABILITIES OF STUDENTS OF THE TECHNICAL HIGHER EDUCATIONAL INSTITUTION